AFFECT OF COVID-19 ON TELECOM SECTOR IN INDIA- A REVIEW - Gurpreet Singh, Dr. Sanjeev Kumar Garg (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The telecom industry is one of the fastest-growing sectors in India, So this article is going to trace the effect of COVID 19 or coronavirus pandemic on the telecom industry. The report is also going to know about consumer retention after the entry of Reliance Jio. The articles also discuss how reliance Jio affects the telecom industry. It will highlight all the current changes in the telecom industry. Here we also have the reasons to discuss why a big market player Vodafone and airtel have to change their marketing strategy? Global telecom service providers play a significant and vital role in the ongoing COVID 19 pandemic. Before the pandemic, people choose their workplace to do their work in a single network, but while being at home, this thing is not possible after the announcement of the government that all the official(private sector) should work from home. The burden on telecom grows up to 40-60%, whereas peoples who are at home and having nothing to do with outings they prefer to indulge in chatting, browsing, surfing, playing games, and much more stuff, which puts an extra load of service provided. But the way the telecom industry handles the situation is far better than expected.